Philosophy of Justice In The Shadow of Plurality A Feminist Interpretation of Legal Inequality Towards Women - Fitria Wildasari; Sidik Sunaryo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This article explores the critical relationship between justice, feminist jurisprudence, and legal pluralism in the context of Indonesia's multilayered legal system. While classical legal philosophy particularly Aristotelian thought has long conceptualized justice in terms of distributive and corrective fairness, such frameworks often fall short in addressing systemic gender inequality. In societies marked by legal pluralism, including Indonesia, women remain structurally marginalized within state law, customary law, and religious law. This study examines how feminist jurisprudence provides an alternative lens for reinterpreting justice by centering the lived experiences of women and exposing patriarchal power structures embedded in legal institutions. Feminist jurisprudence challenges the presumed neutrality of law, revealing its complications in reinforcing male dominance and silencing women's voices. In the plural legal landscape of Indonesia, patriarchal norms are often preserved through the state's accommodation of discriminatory practices under the guidance of respecting cultural traditions or religious autonomy. Customary inheritance laws, the positioning of women in marriage, and religious family law disproportionately disadvantage women. Despite formal legal reforms such as the enactment of the Domestic Violence Law and the Sexual Violence Law, implementation remains hindered by institutional gender bias and cultural resistance. By integrating feminist legal theory into the discourse on justice, this paper advocates a shift from formal equality to substantive, transformative justice. Legal pluralism, rather than being a neutral space of cultural expression, must be critically interrogated to prevent the legitimization of systemic gender oppression. Ultimately, the article argues that feminist jurisprudence offers both a theoretical and practical pathway for reconstructing inclusive legal systems that uphold the rights and dignity of women in pluralistic societies.